Tinjauan Pustaka Sistematis: Program Kantin Kejujuran untuk Meningkatkan Karakter Jujur di Sekolah Dasar - Lintang Indah Cahyani; Muhamad Taufik Hidayat (University of Muhammadiyah Malang, 2023)
Dishonest behavior, such as corruption, bribery, etc., is often encountered. It is certainly contrary to the goals of national education. The character of honesty in elementary schools in Indonesia still needs to be instilled in students, considering that the honesty of students in elementary schools is still low. This study aims to analyze the strategy for implementing an honesty canteen, the obstacles to implementing an honesty canteen and the results of implementing an honesty canteen program in improving the honest character of students in elementary schools. The method used in this paper is a systematic literature review. The data at this writing uses articles from Google Scholar spanning the last ten years discussing the honesty canteen program. Data were analyzed using the keywords honesty canteen and honesty character. An assessment technique to check the validity of the data is carried out using source triangulation. The results of this study show that (1) the strategy for implementing the honesty canteen must involve the involvement of teachers, students, as well as all people in the school environment, (2) the lack of honest canteen management in elementary schools makes it difficult for students to return their returns. It is because sometimes there is no small money in the canteen. (3) the honesty canteen is carried out through a self-service system program; students carry out personal services at the stages of product transaction needs through this system. Students are trained to be honest when buying meals at the honesty canteen.